Pola Shift Perawat di Masa Pandemi COVID-19 - Kartika Mawar Sari Sugianto; Rr. Tutik Sri Hariyati; Annisa Rahmi Galleryzki (Journal of Telenursing (JOTING), 2021)
This study aims to determine the shift patterns used by the hospital during the pandemic. The research design uses systematic reviews through online databases such as Science Direct, EBSCOhost, Scopus, ProQuest, Google Scholar, and other search sources. The article selection process uses the PRISMA method. The number of articles obtained was 795, and then only 11 were used in this review. The results of this study indicate that the shift pattern during the pandemic period includes (1) 12 hours per shift; (2) 6 hours per shift; (3) 4-8 hours divided into shifts; (4) pattern 7-7-10; (5) flexible work schedules, short intervals; (6) three stages of rotation and a 14 day quarantine plan. In conclusion, the 12 or 6 hour shift pattern without a break is not suitable for nurses' health, while other shift patterns tend to pay attention to the health and safety of nurses during a pandemic. Keywords: Pandemic COVID-19, Nurse Shift Pattern